1996
DOI: 10.1111/j.1471-6402.1996.tb00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Dating Risk Factors for Sexual Assault Among College Women

Abstract: American societal norms frequently link alcohol, dating, and sexuality. This cross‐sectional study examined the role of alcohol and dating risk factors for sexual assault among a representative sample of female students at a large urban university. Over half of the 1,160 women had experienced some form of sexual assault. Ninety‐five percent of these assaults were committed by someone the woman knew and almost half of these assaults involved alcohol consumption by either the man, the woman, or both. Discriminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
329
5
9

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 349 publications
(372 citation statements)
references
References 31 publications
29
329
5
9
Order By: Relevance
“…Eighty-four percent of the women knew their assailant; 57% were dates. These findings have been replicated by other researchers at various universities (Abbey, Ross, McDuffie, & McAuslan, 1996a;Kalof, 1993;Mills & Granoff, 1992;Muehlenhard & Linton, 1987;Neal & Mangis, 1995). Recently, Brener, McMahon, Warren, and Douglas (1999) examined the prevalence of rape among a representative sample of 4609 female college students.…”
Section: Samples Of College Womenmentioning
confidence: 60%
See 4 more Smart Citations
“…Eighty-four percent of the women knew their assailant; 57% were dates. These findings have been replicated by other researchers at various universities (Abbey, Ross, McDuffie, & McAuslan, 1996a;Kalof, 1993;Mills & Granoff, 1992;Muehlenhard & Linton, 1987;Neal & Mangis, 1995). Recently, Brener, McMahon, Warren, and Douglas (1999) examined the prevalence of rape among a representative sample of 4609 female college students.…”
Section: Samples Of College Womenmentioning
confidence: 60%
“…Rates of alcohol consumption vary among different ethnic groups, thus rates of alcoholinvolved sexual assault are also likely to differ (Office of Applied Statistics, 1997). Abbey et al (1996a) found that alcohol was involved in fewer of the sexual assaults that African American women experienced as compared to Caucasian women, although the crosssectional predictors of sexual assault did not vary by ethnicity. This study, however, assessed only a limited number of variables, therefore, research that includes more detailed questions about alcohol's role in sexual assault may find differences.…”
Section: Surveys With Perpetrators and Victimsmentioning
confidence: 80%
See 3 more Smart Citations